STUDY ON THE EXPERIMENTAL TECHNIQUES OF DYNAMIC FRACTURE TOUGHNESS OF MATERIALS BASED ON INSTRUMENTED CHARPY IMPACT TEST - XU ZhenQi; ZHU ShiFan; GUO ChunHuan; WANG YanChun; JIANG FengChun (Jixie qiangdu)
A measuring method was proposed to evaluate the dynamic fracture toughness of materials using pre-cracked Charpy impact specimens in this work. Different from the previous methods,a simple way to calculate the dynamic stress intensity factors of three-point bending specimen was developed based on the calculation of fracture specimen’s stiffness using Timoshenko beam theory. The fracture initiation time was detected experimentally and then used to determine the dynamic fracture toughness of materials. The calculated values were compared with the results obtained from finite element simulation,a good agreement was found from the comparison between the theoretical calculation and FEA,indicating that the current method proposed in this study is accurate,reliable and convenient for engineering application.